(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Urban mobility is the lifeline for functioning of a city that provides connectivity between home,workplace, educational institutes and all other places of day-to-day needs. While commutability plays apivotal role in overall transportation planning of a city, increased affordability has seen a correspondingshift to private mode of transportation in most of the cities, specifically developing countries. Due to thisthere has been an increase in volume of private vehicles which resulted in overwhelming of existingtransport network capacities. Capacity of existing infrastructure is not able to sustain increased usage ofprivate transport causing congestion and chaos undermining the very functioning of the city and as wellaffecting not only human health but overall environmental quality. This has led to the need to identifyand explore more efficient and sustainable modes of public transport options such as multimodetransport system like metro rail, bus rapid transport etc. However, to enhance overall commutingexperience of metro rail, we need to enhance the options of first and last mile connectivity. Metro greatlyenhances urban livability with unhindered commutes and also has benefits of environment friendly modeof transportation. First and last mile connectivity (FLMC) at the origin and destination of the metrocompletes the commute comprehensively and contributes to users‟ quality of life in general. Options ofropeway and tramway seems to be viable options to address the complexities of First and last mileconnectivity (FLMC),land-use, street network, topography, interactions of physical infrastructure at themetro stations and its surroundings.